Perceptions of Artificial Intelligence (AI) Usage on Auditor Judgment - Widya Ais Sahla; Dwianto Mukhtar Latif (Indonesian Journal of Applied Accounting and Finance, 2023)
This research aims to examine the relationship between perceptions of the use of Artificial Intelligence (AI) in audit practices and Auditor Judgment in financial audits. A survey method is used to involve students majoring in Accounting as respondents. Data was collected through a specially designed questionnaire and statistical analysis was used to test the hypothesis. The research results reveal that there is a significant influence between the perception of the use of AI in auditing and the auditor's ability to make judgments. Auditors who have a positive perception of AI tend to make more accurate judgments in evaluating the audit entity's financial reports. To the best of our knowledge, this is the first study that exploring a relationship that is still rarely explored in the literature, namely the influence of perceptions of the use of AI in auditing on the Auditor's Judgment ability. This research also provides new insights into how AI technology can contribute as a valuable tool in improving quality in the audit process